Evolving Design Pedagogies: Broadening Universal Design for Social Justice - Lanteigne, Victoria; Rider, Traci Rose; Stratton, Peter (Enquiry The ARCC Journal for Architectural Research, 2022)
Universal Design came into prominence as a successor to the Americans with Disabilities Act (ADA), contributing to broader notions of accessibility beyond baseline codes and standards. Rooted in human factors research, Universal Design primarily centers on supporting human performance through the development of accessible and usable environments (Steinfeld and Maisel 2012, 95-96). As such, Universal Design pedagogies predominantly focus on enhancing environments for people with disabilities and aging populations (O Shea 2018, 721; Steinfeld and Maisel 2012, 49). However, some believe Universal Design is on the cusp of a paradigm shift to address broader aspects of social justice (Salmen 2012; Steinfeld and Maisel 2012, 159-160). This paper synthesizes existing literature to explore how current academic and practice-facing Universal Design pedagogies support the movement’s expansion to address social justice across demographic groups. Critical audiences for this work include architectural educators, students, researchers, policymakers, and building professionals interested in advancing the theory and practice of Universal Design. Recommendations from this work reposition Universal Design pedagogies as a pathway for creating more equitable and inclusive buildings, spaces, and communities that are truly designed for all.